Drill learning and practice method: Improving student learning outcomes on number counting operations round - Mardia, Ainal; M, Bakri; Sukayasa, Sukayasa; Mubarik, Mubarik (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research is classroom action research that aims to improve student learning outcomes by using the drill and practice method in the direct learning model. The application of the direct learning model follows the following phases: 1) conveying the objectives and preparing the learners, 2) demonstrating knowledge or skills, 3) guiding the training, 4) checking understanding and providing feedback, and 5) providing opportunities for further training and application. This research was carried out in as many as two cycles by following predetermined stages. The subject of this study is 7th-grade students of SMP Negeri 1 Sindue Tobata, with a total of 23 students. The results of the research from Cycle I and Cycle II showed an increase in student learning in integer counting operations learning using the drill and practice method in the direct learning model, namely in Cycle I by 60.8% and in Cycle II by 87%. Therefore, the drill and practice learning method can improve student learning outcomes in learning integer counting operations.